Development of a gene carrier using a triblock co-polyelectrolyte with poly(ethylene imine)-poly(lactic acid)-poly(ethylene glycol). (May 2017) - Sim, Taehoon; Park, Gayoung; Min, Hyeyoung; Kang, Soowon; Lim, Chaemin; Bae, Sungmin; Lee, Eun Seong; Youn, Yu Seok; Oh, Kyung Taek
The success of gene therapy mainly depends on the carriers for effective gene delivery. A non-viral vector using a cationic block co-polyelectrolyte, PEI-PLA-PEG polyethyleneimine-poly(lactic acid)-poly(ethylene glycol)) was developed as a potential gene carrier. The cationic PEI-PLA-PEG showed less toxicity compared to PEI and formed a gene nanocomplex (termed polyplex) by interaction with plasmid DNA or small interference RNA. The polyplex showed smaller particle size and greater positive zeta potential by increasing the high polymer nitrogen/DNA phosphate ratio. The polyplex with a nitrogen/DNA phosphate ratio of 16 or 32 demonstrated higher gene transfection by fluorescence imaging, flow cytometry measurement, and β -galactosidase activity. In particular, the polyplex with therapeutic histone deacetylase small interference RNA at nitrogen/DNA phosphate ratio 16 showed the most favorable properties with definite tumor growth inhibition. The synthetic PEI-PLA-PEG also showed less toxicity and would, therefore, be a great potential gene carrier, particularly given that small interference RNA delivery does not increase the charge density of small interference RNA due to the formation of a stable complex through conjugation with PLA-PEG.